Ethical aspects in telemedicine. Literature review - Rosero-Villarreal, Francisco; Sánchez del Hierro, Galo (Acta Bioethica, 2024)
This paper analyzes the ethical aspects related to telemedicine. A literature search on the topic was conducted, based on a systematic review of the specific ethical aspects of telemedicine using thirteen articles selected from the Web of Science and PubMed databases. The findings were grouped into the following categories: access; principles; quality of care; privacy, confidentiality, cybersecurity; commercialization, conflict of interest; trust and doctor-patient relationship; education, training and licensing; professional malpractice, telenegligence; virtual prescription of medications; shared decisions, patient empowerment; informed consent; governance and policies. The ethical aspects of telemedicine are important not only for adequate health care, but also for the construction of adequate public policies.